Monopoly Media: Efforts to Increase the Activity of Elementary School Students in Learning Animals Movement Organs - Luh Ayu Ratna Sawitri Prabali; Adrianus I Wayan Ilia Yuda Sukmana (Jurnal Ilmiah Sekolah Dasar, 2021)
The low learning outcomes of fifth-grade students are caused by the lack of thematic learning media. Therefore, this study aimed at developing simple monopoly learning media on the subtheme of animal movement organs. The design of this study was development research based on ADDIE model. The collected data in this study were qualitative and quantitative data. The subjects in this study were a material expert, a media expert, an instructional design expert, and a learning practitioner. The data were collected through questionnaire. Then, the collected data were analyzed using descriptive qualitative and descriptive quantitate method.Â  The results of this study show that the simple monopoly learning media developed is valid based on a review of material experts, reviews of learning media experts, and reviews of learning design experts with very good qualifications. Meanwhile, this learning media has good qualification to be used in thematic learning on the subtheme of animal movement organs. It is based on the result of teacherâ€™s response to the developed media. It can be concluded that the monopoly learning media is suitable to in the thematic learning specially for learning animal movement organs. The implication of the result of this study is that it can help students be actively involved in meaningful and fun learning.